Cannabis in epilepsy: From clinical practice to basic research focusing on the possible role of cannabidivarin. Issue 3 (19th September 2016) - Morano, Alessandra; Cifelli, Pierangelo; Nencini, Paolo; Antonilli, Letizia; Fattouch, Jinane; Ruffolo, Gabriele; Roseti, Cristina; Aronica, Eleonora; Limatola, Cristina; Di Bonaventura, Carlo; Palma, Eleonora; Giallonardo, Anna Teresa
Summary: Cannabidivarin (CBDV) and cannabidiol (CBD) have recently emerged among cannabinoids for their potential antiepileptic properties, as shown in several animal models. We report the case of a patient affected by symptomatic partial epilepsy who used cannabis as self‐medication after the failure of countless pharmacological/surgical treatments. Clinical and video electroencephalogram (EEG) evaluations were periodically performed, and the serum levels of CBDV, CBD, and Δ9‐tetrahydrocannabinol were repeatedly measured. After cannabis administration, a dramatic clinical improvement, in terms of both decrease in seizure frequency and recovery of cognitive functions, was observed, which might parallel high CBDV plasma concentrations. To widen the spectrum of CBDV possible mechanisms of action, electrophysiological methods were applied to investigate whether it could exert some effects on γ‐aminobutyric acid (GABA)A receptors. Our experiments showed that, in human hippocampal tissues of four patients affected by drug‐resistant temporal lobe epilepsy (TLE) transplanted in Xenopus oocytes, there is decrease of current rundown (i.e., reduction of use‐dependent GABAA current) after prolonged exposure to CBDV. This result has been confirmed using a single case of Rasmussen encephalitis (RE). Our patient's electroclinical improvement supports the hypothesis that cannabis could actually represent an effective, well‐tolerated antiepileptic drug. Moreover, the experimental data suggest that CBDV may greatly contribute to cannabis anticonvulsant effect through its possible GABAergic action.